The levels and predictors of physical activity engagement within the treatment seeking transgender population: a matched control study - Jones, B.A.; Haycraft, E.; Bouman, Walter Pierre; Arcelus, Jon (Human Kinetics, 2018)
Background: Physical activity has been found to alleviate mental health problems and could be beneficial for at-risk populations, such as transgender people. This study had three aims. First, to explore the amount of physical activity that treatment seeking transgender people engage in, and to compare this to matched cisgender people. Second, to determine whether there was a difference in physical activity depending on cross-sex hormone use. Third, to determine factors which predict physical activity among treatment seeking transgender people. Method: Transgender (n=360) and cisgender people (n=314) were recruited from the UK. Participants were asked to complete questionnaires about physical activity, symptoms of anxiety and depression, self-esteem, body satisfaction and transphobia. Results: Transgender people engaged in less physical activity than cisgender people. Transgender people who were on cross-sex hormones engaged in more physical activity than transgender people who were not. In transgender people on cross-sex hormones, high body satisfaction was the best statistical predictor of physical activity while high self-esteem was the best statistical predictor in people who were not. Conclusion: Transgender people are less active than cisgender people. Cross-sex hormone treatment appears to be able to indirectly increase physical activity within this population, which may be beneficial for mental well-being.